A case report: extensive myocardial calcification and non-ischaemic cardiomyopathy related to past sepsis. Issue 2 (18th February 2021) - Lim, Anthony; Be, Kim Kuy; Wong, Chiew
Abstract: Background: Diffuse myocardial calcification following severe sepsis is a rare complication whose long-term effects are not well-understood. Case summary: A 51-year-old man presented with a 6-month history of worsening dyspnoea on a background of sepsis 9 years prior. His initial echocardiogram showed moderate systolic dysfunction and a mildly dilated left ventricle. Cardiac computed tomography showed signs of mild coronary artery disease without significant stenosis, but the diffuse extensive left ventricular (LV) mid-myocardial calcification was visible. Cardiac magnetic resonance imaging showed diffuse extensive LV mid-myocardial late gadolinium enhancement in keeping with the calcification. He was diagnosed with non-ischaemic cardiomyopathy. He was commenced on appropriate anti-failure medical therapy, maintains New York Heart Association functional class II functional status, and has received a prophylactic implantable cardioverter-defibrillator. Discussion: Diffuse myocardial calcification might be associated with long-term development of non-ischaemic cardiomyopathy. The benefit of monitoring such patients for long-term effects is not routine, but should be considered.